Relating seafloor geomorphology to subsurface architecture: How mass‐transport deposits and knickpoint‐zones build the stratigraphy of the deep‐water Hikurangi Channel. Issue 7 (23rd July 2021) - Tek, Daniel E.; McArthur, Adam D.; Poyatos‐Moré, Miquel; Colombera, Luca; Patacci, Marco; Craven, Benjamin; McCaffrey, William D.
Abstract: Monitoring of modern deep‐water channels has revealed how migrating channel‐floor features generate and remove stratigraphy, improving understanding of how channel morphologies relate to their deposits. Here, seafloor and subsurface data are reconciled through an integrated study of high‐resolution bathymetry and three‐dimensional seismic data imaging a ca 150 km stretch of the trench‐axial Hikurangi Channel, offshore New Zealand. On the seafloor, terraced channel‐walls bound a flat, wide, channel‐floor, ornamented with three scales of features that increase then decrease in longitudinal gradient downstream, and widen downstream: cyclic‐steps, knickpoints and knickpoint‐zones (in increasing size). Mass‐transport deposits derived from channel‐wall collapse, are bordered by wide and flat reaches of channel‐floor upstream and by knickpoint‐zones (reaches containing multiple knickpoints) downstream. In the subsurface, recognition of ten seismofacies and five types of surface enables identification of four depositional elements: channel‐fill, sheet or terrace, levée, and mass‐transport deposits. Integration of subsurface and seafloor interpretations reveals that knickpoint‐zones initiate on the downstream margins of channel‐damming mass‐transport deposits; they migrate and incise through the mass‐transport deposits and weakly‐confined deposits formed upstream, as the channel tends towards equilibrium. Downstream of a knickpoint‐zone, a flat channel‐floor is bounded by newly‐formed terraces. Knickpoints migrate by eroding upstream and depositing downstream, generating filled concave‐up (cross‐sectional) surfaces in their wake. Within knickpoint‐zones, knickpoint‐generated surfaces are re‐incised by subsequently‐passing knickpoints to produce a composite bounding surface; this surface does not delineate the morphology of any palaeo‐conduit. The Hikurangi Channel's subsurface architecture records the localized erosional response to mass‐transport deposit emplacement via knickpoint‐zone migration, showcasing how transient seafloor features can build channelized stratigraphy. This model provides an additional mechanism to conventional models of channel deposit formation through 'cut‐and‐fill' over long stretches of channel. These findings may aid subsurface interpretation in systems lacking a contemporary self‐analogue or with poor data coverage.